Analisis Kekerasan Seksual Dalam Novel Mayday Mayday Karya Laili Muttamimah Dan Implikasinya Pada Pembelajaran Sastra Di SMA - Devina Putri; Lazarus Linarto; Yuliati Eka Asi; Petrus Poerwadi; Bernadus Andi; Petrisia Agustini (Universitas Palan, 2023)
This research discusses sexual violence against the main female character in the novel Mayday Mayday by Laili Muttamimah. Therefore, this study aims to describe: (1) the form of sexual violence experienced by the female protagonist in the novel Mayday Mayday, (2) the implications for learning to identify novels for grade XI high school students.This research uses a qualitative approach. The data source of this research is the novel Mayday Mayday. The object of this research is all forms of sexual violence experienced by the main female character in the novel Mayday Mayday. The results of this study are as follows: (1) The forms of sexual violence contained in the novel Mayday Mayday are physical sexual harassment, non-physical sexual harassment, rape, sexual torture, and discrimination of the victim's gender identity. The results of this study are used in short story learning for grade XI high school students, in accordance with KD 3.6 analyzing the message of the novel fiction book read by understanding the content of the message conveyed by the author aims to develop reasoning skills.